Who believes in foreign disinformation? Evidence from a disinformation discernment exercise in Sweden - Charlotte Wagnsson; Albin Östervall (Political Research Exchange)
Authoritarian governments have a history of interfering in the internal information space of democratic states, particularly in relation to national elections. In response to the spread of foreign disinformation, states and organizations have implemented various countermeasures, ranging from bans on outlets and platform regulation to fact-checking initiatives and digital media literacy education. The efficacy of such educational interventions could benefit from being tailored to the varying susceptibilities of different audiences. Previous research on audience differences has primarily highlighted cognitive factors, political orientation, and media consumption as determinants of susceptibility to disinformation, while findings related to demographic influences remain inconclusive. We recently conducted an experimental study in Sweden (n = 1,054) assessing the effects of two video-based media literacy interventions (Wagnsson et al. (2025)). In this study, we repurpose said data to examine demographic predictors of ‘discernment skills’ – the ability to differentiate between reliable news and disinformation. We included two types of educations, one focusing on disinformation in general and one emphasizing the problems with adversarial foreign disinformation. Our findings indicate that both versions enhanced the participants’ skills, and that discernment abilities were associated with being younger, more educated, and male. We provide potential explanations for these correlations and offer recommendations for future research.